Acute effects of kinesio taping on muscular strength and endurance parameters of the finger flexors in sport climbing: A randomised, controlled crossover trial. Issue 4 (20th April 2020) - Limmer, Mirjam; Buck, Susanne; de Marées, Markus; Roth, Ralf
Abstract: Kinesio taping (KT) is a commonly used intervention in sports and, recently, KT has become popular among athletes competing in sport climbing and bouldering events. However, evidence on the effect of KT on grip strength and endurance is still controversial. Therefore, the purpose of this study was to evaluate immediate effects of KT on muscular strength and endurance of the finger flexor muscles in sport climbers. Twenty recreationally-trained active sport climbers (10 men, 10 women) aged 28.5 ± 10.6 years performed one familiarisation trial and subsequently, in a randomised crossover design, two test trials either with (TAPE) or without (CONTROL) KT over the finger flexor muscles. Test trials consisted of three performance measurements (hand grip strength and endurance, finger hang, and lap climbing) at intervals of 48 h in a randomised order. We observed no significant differences in the parameters of hand grip peak force, fatigue index, finger hang time, lap climbing distance and time, or maximum blood lactate values after lap climbing between the TAPE and CONTROL trials ( p  > 0.05). The participants' climbing ability was significantly correlated with the intra-individual performance changes between the TAPE and CONTROL conditions for the fatigue index ( r  = −0.598, p  = 0.005), but not in any of the other performance-related parameters. Therefore, KT over the finger flexor muscles neither enhanced hand grip strength and endurance nor the sport climbing performance parameters of finger hang, lap climbing distance and time, and maximum blood lactate values after lap climbing.